Detrminants of International Migration: Application of the Gravity Model - Pebrianti; Yunisvita; Dwi Melliny, Vinny (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
This study aims to analyze the application of the gravity model by looking at the effect of the Destination Country Labor Force, Home Country Labor Force, Inter-Country GDP Ratio, and Inter-Country Distance on the Number of Indonesian Labor Migration. The data used are time series data from 2013 to 2022 and cross section data on 15 destination countries for Indonesian workers with panel data regression analysis techniques. Based on the results of the Fixed Effect Model (FEM), the Destination Country Labor Force and Inter-Country Distance have a negative and significant effect on the Number of Indonesian Labor Migration, while the Home Country Labor Force and Inter-Country GDP Ratio have a positive and significant effect on the Number of Indonesian Workers. The West Asia region and Saudi Arabia have the lowest intercept values, while the highest intercept values are in the East Asia region and in China. The difference in intercepts shows the difference in the number of Indonesian workers as a whole caused by the different characteristics of each region and country.